Artificial Intelligence (AI) Systems: Implications for Emotional Human Communication - Nwodo, Augustine Uchenna (Transpublika Publisher, 2024)
Artificial intelligence (AI) systems are increasingly designed with affective characteristics. Emotionalized AI machines simulate human emotions to provide emotional assistance to human beings in various areas of life, and in turn, reshaping communication. Both the cognitive and affective aspects of artificial intelligence technology are widely adopted in today’s world due to their positive impact in accomplishing tasks. However, the critical question regarding the implications of AI advancement on the emotional human communication is the crux of this study. Thus, this research work inquired into the implications of artificial intelligence systems on the innate emotional human interaction. Communication research in this area has not received much attention. Therefore, through the use of conceptual research approach, 186 scientific article publications were extracted from Ebsco and Google databases, out of which 47 met the inclusion criteria based on the study objective. Data from these secondary sources were critically analyzed. This study was anchored on the theoretical foundation of Diffusion of Innovation theory. The study argues that though the advancement in artificial intelligence (AI) systems comes with lots of positive values, the intrinsic human-human emotional communication is a greater value that should not be endangered or substituted by technology. Hence, the paper recommends a conscious effort on the part of researchers and manufacturers of artificial intelligence (AI) systems to strictly abide by ethical standards in order to preserve this innate value in the human person.